The growth rate of haemophilus paragallinarum profile in shake flask fermentation ; determination [substrate] critical - Mel, Maizirwan; Sarmidi, Mohd. Roji; Abdul Aziz, Ramlan (Penerbit UTM Press, 2002)
Determination [substrate] critical is important in a fermentation process especially for optimizing coryza vaccine production. The objectives of the study were to establish the effect of different substrates on the production of Hpg cell and to study the effect of different concentration of a selected carbon sources on the specific growth rate of Hpg. The data obtained indicate that fructose produced the highest concentration of cell biomass of Hpg, closely followed by maltose, lactose, glucose, and sucrose. However, from operating cost point of view, glucose was selected as the most suitable carbon source due to its low cost and acceptable Hpg cell yield. The critical glucose concentration was found to be at 0.5 %, which corresponds to specific growth rate Hpg of 0.4 h–1.